Microbiological and metal contamination of watercress in the Wellington region, New Zealand-2000 survey - C. Edmonds; R. Hawke (Elsevier, 2004)
Abstract Objectives: To investigate potential microbiological and metal contamination of watercress and to assess the public health risks associated with harvesting and consumption of watercress. Method: During March and April 2000, samples were taken from 11 known or potential watercress collection sites in the Wellington region. Microbiological testing included bacterial counts for presumptive and faecal coliforms (watercress); total coliforms (growing water); and Escherichia coli (E. coli) and presence/absence tests for Campylobacter species (g rowing water and watercress). Watercress concentrations of a range of metals were also measured. Results: All of the sites showed significant levels of E. coli in samples of both watercress and water. The E. coli levels in water were well above recommended freshwater recreational contact safety guidelines at most sites. Campylobacter was detected in the growing waters at all sites (80% of the samples) and in 11% of the watercress samples. Mean metal concentrations in watercress did not exceed the NZ Food Regulations (1984) levels at any of the sites. However, lead concentrations at the urban sites and one of the semi‐urban sites would have exceeded the new Australia New Zealand Food Standards Code maximum levels (2003). Conclusions and Implications: The consumption of raw watercress contaminated with enteric pathogens could potentially cause serious gastrointestinal illness (e.g. campylobacteriosis) and people gathering watercress could also be at risk of infection from contact with contaminated surface waters.